The Role of Notaries in Preventing Money Laundering Crimes Through the Obligation to Report Suspicious Financial Transactions - Hidayat, Taufik; Winjaya Laksana, Andri (Jurnal Konstatering, 2026)
Notaries hold a strategic position as public officials directly involved in the preparation of legal deeds of high economic value, thus potentially being misused as a means of money laundering. In line with the development of the Anti-Money Laundering and Prevention of Terrorism Financing (APU-PPT) regime, notaries are normatively designated as reporting parties based on Law Number 8 of 2010 concerning Money Laundering. However, in practice, the implementation of this reporting obligation still faces various normative, technical, and ethical challenges, particularly related to conflicts between the reporting obligation and the principle of confidentiality of notary positions as specified in the Notary Law. The purpose of this study is to analyze the basis and urgency of notary involvement in preventing money laundering, identify factors influencing the implementation of a notary's role as a reporting party, and formulate an ideal legal framework to ensure legal certainty for notaries. The research method used is normative legal research with a statutory and conceptual approach, through an analysis of relevant laws and regulations, legal doctrine, and scientific literature. The results indicate that notaries play a highly strategic role in preventing money laundering, acting as gatekeepers, ensuring that legal acts outlined in authentic deeds are truly based on legitimate, transparent, and legally accountable transactions.